2010
DOI: 10.1037/a0020242
|View full text |Cite
|
Sign up to set email alerts
|

Beyond good and evil: The time-course of neural activity elicited by specific picture content.

Abstract: The present study examined electrocortical evidence for a negativity bias, focusing on the impact of specific picture content on a range of event-related potentials (ERPs). To this end, ERPs were recorded while 67 participants viewed a variety of pictures from the International Affective Picture System. Examination of broad categories (i.e., pleasant, neutral, unpleasant) found no evidence for a negativity bias in two early components, the N1 and the Early Posterior Negativity (EPN), but revealed that unpleasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
390
9
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 373 publications
(465 citation statements)
references
References 101 publications
61
390
9
5
Order By: Relevance
“…At posterior parietal leads along the midline The interaction between context and anxiety did not reach significance either, F(1, 56) = .12, p > .10. This analysis also disclosed that the LPP was smaller in high compared to low anxious individuals, F(1, 56) = 4.71, p < .05, in agreement with these previous studies (Foti, Performance monitoring and anxiety et al, 2010;Weinberg & Hajcak, 2010). These control analyses confirmed that the reported FRN effect (and its modulation by levels of trait anxiety and emotional context) did not overlap (in time and electrode locations) with a later LPP effect taking place during feedback processing.…”
Section: Frn Componentsupporting
confidence: 80%
See 2 more Smart Citations
“…At posterior parietal leads along the midline The interaction between context and anxiety did not reach significance either, F(1, 56) = .12, p > .10. This analysis also disclosed that the LPP was smaller in high compared to low anxious individuals, F(1, 56) = 4.71, p < .05, in agreement with these previous studies (Foti, Performance monitoring and anxiety et al, 2010;Weinberg & Hajcak, 2010). These control analyses confirmed that the reported FRN effect (and its modulation by levels of trait anxiety and emotional context) did not overlap (in time and electrode locations) with a later LPP effect taking place during feedback processing.…”
Section: Frn Componentsupporting
confidence: 80%
“…At any rate, future studies are needed to corroborate this statement. Importantly, control analyses showed that the reported FRN results did not overlap with a later LPP effect Schupp et al, 2004), the latter being indicated by a blunted LPP component for high compared to low anxious Performance monitoring and anxiety participants, consistent with previous ERP studies (Foti, et al, 2010;Weinberg & Hajcak, 2010). Our ERP results further show that the effect of feedback valence was only observed in the positive context, where happy faces and "neutral" faces were presented, and that this difference was larger for low, compared to high anxious participants.…”
Section: Selective Alteration Of Performance Monitoring In Anxietysupporting
confidence: 70%
See 1 more Smart Citation
“…It is important to note that there is some overlap between P3 and LPP components, leading to a lack of clarity between studies given the different temporal definitions of LPP employed (see Weinberg & Hajcak, (2010) for a review of the different time windows). To address this Hajcak, MacNamara, & Ovlet (2010) recommend dividing the P3/LPP in multiple time windows following stimulus presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced LPP amplitude was found in relation to visual stimuli that were perceived as silent due to specific task context, such as targets (Azizian, Freitas, Parvaz, & Squires, 2006). Most importantly, it has been frequently reported that LPP amplitude is larger for human faces compared scenes and objects images which implies that faces possess significance that is unique and unequalled by other categorise of visual stimuli such as generic products (Ferri, Weinberg, & Hajcak, 2012;Weinberg & Hajcak, 2010). Similar studies also conclude that images showing human faces appear to attract attention more easily than images that do not present faces (Ito & Cacioppo, 2000).…”
Section: Event-related Potentialsmentioning
confidence: 93%